UMP scores a I00% success rate at two concurrent exhibitions - UMP, PNC (Penerbit UMP, 2009)
UMP reached another milestone as it scored a I 00% success rate at two world class exhibitions which were held at the same time. The two exhibitions which saw UMP participation was the International Invention, Innovation & Technology Exhibition (ITEX) 2009 and the Water Malaysia 2009 exhibition, which were both held in May.